Identification of Genes Selectively Regulated in Human Hepatoma Cells by Treatment With Dyslipidemic Sera and PUFAs. Issue 9 (September 2015) - De Rosa, Maria Caterina; Caputo, Mariella; Zirpoli, Hylde; Rescigno, Tania; Tarallo, Roberta; Giurato, Giorgio; Weisz, Alessandro; Torino, Gaetano; Tecce, Mario Felice
Abstract : Serum composition is linked to metabolic diseases not only to understand their pathogenesis but also for diagnostic purposes. Quality and quantity of nutritional intake can affect disease risk and serum composition. It is then possible that diet derived serum components directly affect pathogenetic mechanisms. To identify involved factors, we evaluated the effect on gene expression of direct addition of dyslipidemic human serum samples to cultured human hepatoma cells (HepG2). Sera were selected on the basis of cholesterol level, considering this parameter as mostly linked to dietary intake. Cells were treated with 32 sera from hypercholesterolemic and normocholesterolemic subjects to identify differentially regulated mRNAs using DNA microarray analysis. We identified several mRNAs with the highest modulations in cells treated with dyslipidemic sera versus cells treated with normal sera. Since the two serum groups had variable polyunsaturated fatty acids (PUFAs) contents, selected mRNAs were further assessed for their regulation by docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA) and arachidonic acid (AA). Four genes resulted both affected by serum composition and PUFAs: 3‐hydroxy‐3‐methylglutaryl‐CoenzymeA synthase 2 (HMGCS2), glutathione S‐transferase alpha 1 (GSTA1), liver expressed antimicrobial peptide 2 (LEAP2) and apolipoprotein M (ApoM). HMGCS2 expression appears the most relevant and was also found modulated via transcription factors peroxysome proliferator activated receptor α (PPARα) and forkhead box O1 (FoxO1). Our data indicate that expression levels of the selected mRNAs, primarily of HMGCS2, could represent a reference of nutritional intake, PUFAs effects and dyslipidemic diseases pathogenesis. J. Cell. Physiol. 230: 2059–2066, 2015. © 2015 Wiley Periodicals, Inc.